Quantified Piper sarmentosum Roxb. leaves aqueous leaf extract and its antihypertensive effect in dexamethasone-induced hypertensive rats - Muhammad Firdaus Azmi,; Amilia Aminuddin,; Jamia Azdina Jamal,; Adila A Hamid,; Azizah Ugusman, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The quality control of raw herbal materials is important to ensure the safety, efficacy, and reproducibility of herbal products. Herbal products with consistent efficacy should be standardized and quantified based on their bioactive phytochemical compounds. Piper sarmentosum Roxb. has been reported for its antihypertensive activity. However, its antihypertensive effect on dexamethasone-induced hypertension still lacks information. In this study, the quality of two batches of raw P. sarmentosum leaf materials was assessed for heavy metal and microbial contents, and their aqueous extracts were assayed for antioxidant activity. The aqueous extract of the second batch of P. sarmentosum leaves was the only extract that passed the heavy metal and microbial limits and had the highest antioxidant activity (50.00 ± 2.88%); therefore, this extract was used for subsequent studies. The extract was quantified for two phytochemical markers, rutin (0.09 ± 0.002%) and vitexin (0.23 ± 0.007%), using a validated ultrahigh performance liquid chromatography method. The quantified extract (500 mg/kg/day orally) was able to lower the systolic blood pressure, diastolic blood pressure, and mean arterial pressure of dexamethasone-induced hypertensive rats comparable to the positive control drug, captopril. In summary, the quantified aqueous extract of P. sarmentosum based on rutin and vitexin lowers the blood pressure of dexamethasone-induced hypertensive rats, but its underlying mechanism warrants further investigation.